Sources of the river : tracking David Thompson across western North America - Nisbet, Jack, 1949- (Sasquatch Books, 1994)
Examines the life of David Thompson, explorer of the Pacific Northwest, fur trader, and cartographer, detailing encounters with Native American cultures, the mapping of the Columbia River, and other wilderness adventures as recorded in his field journals.